PEMANFAATAN KITOSAN CANGKANG KEONG BAKAU (Telescopium sp) SEBAGAI PENGIKAT ION LOGAM TIMBAL (Pb) DALAM LARUTAN - Darman Panggalo; Syaiful Bahri; Ni Ketut Sumarni (KOVALEN: Jurnal Riset Kimia, 2016)
ABSTRACTResearch utilization of mangrove snail chitosan conech shell (Telescopium sp) as a binding metal ions of lead (Pb) in solution. This study aims to determine the best time of the metal ion absorption of lead (Pb) by a conch shell chitosan mangrove (Telescopium sp) with the remains of 150 rpm shaking method. This research was conducted by completely randomized design (CRD) and 4 variations of shaking time is 50, 55, 60 and 65 minutes. Each treatment was repeated three times. The results obtained are binding Pb (II) by the highest chitosan during 65 minutes agitation is 98.27%. Key words: Chitosan, absorption, lead